PENGARUSUTAMAAN GENDER DALAM PEMBANGUNAN PERTANIAN : KASUS PADA PELAKSANAAN PROGRAM FEATI DI KABUPATEN MAGELANG - Dian Maharso Yuwono (Universitas Sebelas Maret, 2013)
Efforts to improve the effectiveness and efficiency of utilization of agricultural resources in order to accelerate the increase in the welfare of farmers cannot be separated from the role of women in agricultural development. Gender mainstreaming in agricultural development is mandated by Presidential Decree No. 9 of 2000. This decree is a strategy to achieve gender equality in development. The gender aspects must be integrated in policy formulation and program activities from planning to evaluation. This paper aims to reveal the women role in the program implementation of Farmer Empowerment through Agricultural Technology and Information (FEATI) in Magelang District-Central Java that integrates gender mainstreaming.